The surface area of the sphere:
A = 4 r² π
1 ) r = 60 m;
A = 4 · 60² π = 4 · 3600 π = 14,400 π m²
2 ) Diameter of 14 cm:
r = 14 cm / 2 = 7 cm
A = 4 · 7² π = 4 · 49 π = 196 π cm²
Answer:
B. 0.694
Step-by-step explanation:
Probability is the ratio of the number of possible outcome to the number of total outcome.
Given that the pain reliever is advertised as being 97% effective, for it to be effective in 12 independent trials
= (97%) ^ 12
= 0.693842361
The is approximately 0.694 to 3 decimal places
Answer:
Yes
Step-by-step explanation:
4 x 3 = 12
5 x 3 = 15
![\boxed{(x - a)(x - b) = 0}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%28x%20-%20a%29%28x%20-%20b%29%20%3D%200%7D)
The equation above is the intercept form. Both a-term and b-term are the roots of equation.
![x = - \frac{1}{3} \\ x = 5](https://tex.z-dn.net/?f=x%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5C%5C%20x%20%3D%205)
These are the roots of equation. Therefore we substitute a = - 1/3 and b = 5 in the equation.
![(x + \frac{1}{3} )(x - 5) = 0](https://tex.z-dn.net/?f=%28x%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%28x%20-%20%205%29%20%3D%200)
Here we can convert the expression x+1/3 to this.
![x + \frac{1}{3} = 0 \\ 3x + 1 = 0](https://tex.z-dn.net/?f=x%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%3D%200%20%5C%5C%20%203x%20%2B%201%20%3D%200)
Rewrite the equation.
![(3x + 1)(x - 5) = 0](https://tex.z-dn.net/?f=%283x%20%2B%201%29%28x%20-%205%29%20%3D%200)
Simplify by multiplying both expressions.
![3 {x}^{2} - 15x + x - 5 = 0 \\ 3 {x}^{2} - 14x - 5 = 0](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%20-%2015x%20%2B%20x%20-%205%20%3D%200%20%5C%5C%203%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%20-%205%20%3D%200)
<u>Answer</u><u> </u><u>Check</u>
Substitute the given roots in the equation.
![3 {(5)}^{2} - 14(5) - 5 = 0 \\ 75 - 70 - 5 = 0 \\ 75 - 75 = 0 \\ 0 = 0](https://tex.z-dn.net/?f=3%20%7B%285%29%7D%5E%7B2%7D%20%20-%2014%285%29%20%20-%205%20%3D%200%20%5C%5C%2075%20-%2070%20-%205%20%3D%200%20%5C%5C%2075%20-%2075%20%3D%200%20%5C%5C%200%20%3D%200)
![3( - \frac{1}{3} )^{2} - 14( - \frac{1}{3}) - 5 = 0 \\ 3( \frac{1}{9} ) + \frac{14}{3} - 5 = 0 \\ \frac{1}{3} + \frac{14}{3} - \frac{15}{3} = 0 \\ \frac{15}{3} - \frac{15}{3} = 0 \\ 0 = 0](https://tex.z-dn.net/?f=3%28%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%5E%7B2%7D%20%20-%2014%28%20-%20%20%5Cfrac%7B1%7D%7B3%7D%29%20-%205%20%3D%200%20%5C%5C%203%28%20%5Cfrac%7B1%7D%7B9%7D%20%29%20%2B%20%20%5Cfrac%7B14%7D%7B3%7D%20%20-%205%20%3D%200%20%5C%5C%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B14%7D%7B3%7D%20%20-%20%20%5Cfrac%7B15%7D%7B3%7D%20%20%3D%200%20%5C%5C%20%20%5Cfrac%7B15%7D%7B3%7D%20%20-%20%20%5Cfrac%7B15%7D%7B3%7D%20%20%3D%200%20%5C%5C%200%20%3D%200)
The equation is true for both roots.
<u>Answer</u>
![\large \boxed {3 {x}^{2} - 14x - 5 = 0}](https://tex.z-dn.net/?f=%20%5Clarge%20%5Cboxed%20%7B3%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20-%205%20%3D%200%7D)